Interpersonal Communication Competence of Faculty of Communication Sciences Alumni - Jauhar Majid Prawiananda; Yulianti (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. This study aims to analyze the profile of interpersonal communication competence among 2023 graduates of the Faculty of Communication Sciences, Universitas Islam Bandung, using the ten-dimensional Interpersonal Communication Competence Scale (ICCS) framework. A quantitative descriptive method was applied, surveying 106 alumni selected via purposive sampling. Data gathered through online questionnaires were analyzed using descriptive statistics. Results revealed that the graduates' overall interpersonal communication competence is highly effective, indicated by an overall mean score of 2.148 (where lower scores denote higher frequency). Even development across all ten dimensions was observed; supportiveness (M = 1.90) and immediacy (M = 1.94) emerged as the most prominent dimensions, reflecting strong relational warmth and supportive behaviors. In contrast, self-disclosure (M = 2.49) and social relaxation (M = 2.48) showed more selective tendencies, indicating calculated self-regulation in professional environments. In conclusion, the 2023 graduates possess adaptive and robust soft skills required to navigate post-pandemic professional interactions, providing vital considerations for curriculum development in communication management.